Potencialidades dos Estudos de Aula para a formação continuada de um grupo de professores que ensinam Matemática na Rede Municipal de São Paulo no contexto de uma pesquisa envolvendo implementação curricular. - Martins, Priscila Bernardo (2020)
This study is part of a Research Project that is part of the set of research produced at the CCPPM Group. This investigation had as its central question: To what extent aspects of the methodology of Classroom Studies can contribute to the continued formation of a group of teachers who teach Mathematics in the Interdisciplinary Cycle in the Municipal Network of the City of São Paulo in a context of curricular implementation?.This is a qualitative research of an interpretive nature, whose strategy used for data collection was triangulation. The theoretical framework is based on authors such as: Curi e Pires (2008); Gatti e Barreto (2009); Ponte (1992, 1998); Tardif (2000, 2002); Shulman (1986, 1987, 2005); Ball, Thames e Phelps (2008); GómezChacón (2003); Curi (2004); Schön (1987); Alarcão (2005); Nóvoa (1992); Boavida e Ponte (2002); Fiorentini (2006), among others. The data show that participation in a collaborative and reflective process of planning agendas and activities, observing and analyzing the actions carried out in the classroom, systematic and incessant reflection on the action and on the action in the scenarios of learning, enabled the professional development of the participants in the Interdisciplinary Cycle meetings and gave more quality to the training of teachers and researchers who teach Mathematics in Basic Education. The research results also show that the Research Project developed in the Classroom Studies, promoted many situations of reflection from the investigation of the praxis, allowing the group of teachers of the Interdisciplinary Cycle to become protagonists of their own professional development, which values their knowledge of experience and consolidates knowledge in action and about action and intensifies them by socializing in a collaborative and reflective work centered on dialogue, negotiation, trust and respect, with a view to improving the students' learning results.